Laying the Foundations : Manual of the British Museum Iraq Scheme Archaeological Training Programme - MacGinnis, John (Archaeopress Publishing, 2022)
Laying the Foundations, which developed out of the British Museum's 'Iraq Scheme' archaeological training programme, covers the core components for putting together and running an archaeological field programme. The focus is on practicality. Individual chapters address background research, the use of remote sensing, approaches to surface collection, excavation methodologies, survey with total (and multi) stations, use of a dumpy level, context classification, on-site recording, databases and registration, environmental protocols, conservation, photography, illustration, post-excavation site curation and report writing. While the manual is oriented to the archaeology of Iraq, the approaches are no less applicable to the Middle East more widely, an aim hugely facilitated by the open-source distribution of translations into Arabic and Kurdish.